Degenerative Effect of Cisplatin on Testicular Germinal Epithelium - Daryosh Mohammadnejad; Ali Abedelahi; Jafar Soleimani-rad; Ameneh Mohammadi-roshandeh; Morteza Rashtbar; Ayda Azami (Tabriz University of Medical Sciences, 2012)
Purpose: The present study was designed to explore the effect of intraperitoneal administration of cisplatin in germinal epithelium of mice. There are few reports on the side effect of cisplatin on spermatogenesis when are used as anticancer drug. Therefore, in the present study the effect of cisplatin on spermatogenesis was evaluated by electron microscopy. Methods: Twenty balb/c mice aging 6-8 weeks was used in this study. The mice were divided into two groups, control and cysplatin treated. cysplatin was injected for five days as 2.5 mg /kg. The mice were sacrificed after 5 weeks and testicular specimens were removed, fixed in boueins, formaldeyd fixative and 2.5% Glutaraldehide then prepared for light and electron microscopic study. Results: Observation with optic microscope in treated group thickness of germinal epithelium was reduced a lot and increased the number of apoptotic cells. In some seminiferous tubules only sertoli cells were observed and nucleus of spermatogony cells was hetrochromatin. The electron microscopic observations showed some irregularity waviness and thickening in basal layer. Also myoid cells of this group were thick and contracted. In this group many apoptotic cells and damaged organelles were seen. Conclusion: It was indicated that cisplatin affected testicular germinal epithelium by both cytotoxic effect and induction of apoptosis.